Aristotle on the value of friends - Kim, B (2018)
In this dissertation, I argue that Aristotle’s account of friendship is egoistic. Focusing on the Nicomachean Ethics, I begin with VIII.2. Here Aristotle claims that in all friendships, friends love only because of the lovable (φιλητόν), which divides into the useful, pleasant, and good. I argue that “because of (διὰ)” refers to at least the final cause and that “the lovable” refers to what appears to contribute one’s own happiness (εὐδαιμονία); therefore Aristotle claims that in all friendships, friends love only for the sake of their own happiness. This result may seem incompatible with some types of concern Aristotle principally attributes to his normative paradigm of complete friendship: wishing goods for the sake of the other and loving the other for himself. One might argue that these types of concern are altruistic, and so it cannot be the case that in all friendships, friends love only for the sake of their own happiness. I argue that these types of concern ultimately hinge on one’s own happiness. The object is the lovable (what appears to contribute to one’s own happiness), specifically the good instantiated by the other’s virtue; further, what a virtuous person takes as valuable about another’s virtue is how it facilitates her own virtuous activity, that is, her own happiness. From here I turn to Aristotle’s notion of “another self.” One popular interpretation of other selfhood defies the altruism/egoism divide. Here the essential feature of other selfhood is virtue, which allows for no prioritization among virtuous people; there is no prioritization of the other over oneself (as in altruism) nor of oneself over the other (as in egoism), since the relevant parties are equal in moral standing (they are virtuous). Assessing the instances of “another self” in the Nicomachean Ethics VIII.12, IX.4, and IX.9, I argue for an egoistic interpretation of other selfhood; the essential feature of other selfhood is involvement in one’s own actualization. That is, what makes other selves valuable is how they facilitate one’s own virtuous activity, one’s own happiness. Finally, I address the doctrine of self-love in the Nicomachean Ethics IX.8. Again, some interpreters derive non-prioritization from the text; Aristotle claims that all virtuous people identify with the understanding (νοῦς), so, the non-prioritization interpretation goes, there can be no prioritization among virtuous agents, as they are identical in the relevant way. I argue for an egoistic interpretation of IX.8; Aristotle endorses praiseworthy self-love, which involves maximizing the superlatively valuable fine (καλὸν) for oneself over others. Moreover, such self-prioritization occurs precisely by gratifying the understanding, that which was supposed to ground non-prioritization.